Haemolytic anaemia and myasthenia gravis - Bessa, I. (1999)
The authors present the case of a healthy 16 year old caucasian female, who complained of weakness, headaches, dizziness and tachycardia in February of 1993. Clinical examination revealed accentuated pallor. Laboratory values were compatible with a cryoglobulin induced haemolytic anaemia. She was treated with prednisolone. After 8 days of corticotherapy, and clinical improvement, she was discharged from hospital. Sixteen months later the clinical symptoms returned with weakness, exhaustion, diplopia, without haemolysis but with leucopenia. Neurological examination was compatible with the diagnosis of myasthenia gravis. is diagnosticated. The thymus was surgically removed and histology revealed lymphoid hyperplasia. The patient started pyridostigmine bromide. Presently the patient is clinically well, but continues to have a leucopenia with lymphocytosis. ln reference to this case, the authors comment on cryoglobulin induced haemolytic anaemia and myasthenia gravis, it's rarity and coexistence in a patient with immunological disorders.